MODULATED KINESIOTHERAPY IN PATIENTS WITH COMPLICATED CORONARY HEART DISEASE - A. I. Olesin; A. V. Belova; Z. Yu. Smolin (Российский кардиологический журнал, 2012)
Aim. To study the effects of modulated kinesiotherapy (MK) on the clinical course of atrial fibrillation (AF) and chronic heart failure (CHF) in patients with coronary heart disease (CHD). Material and methods. The study included 175 patients, aged 46-65 years, with CHD and/or essential arterial hypertension, persistent AF, and Functional Class (FC) I-II CHF. All participants underwent general clinical examination, 6-minute walk test, and assessment of quality of life (QoL), hemodynamic parameters, atrial late potentials, and P wave dispersion. After selection of anti-recurrent AF therapy, all patients were followed up for one year. After that, MK was administered to 119 individuals (68,0%), while the rest of the subjects continued anti-recurrent AF treatment. Results. The combination of MK and anti-recurrent AF therapy was associated with improved QoL and left ventricular diastolic function, reduced CHF FC and AF recurrence rates, and decreased left atrium volume and prevalence of atrial late potentials or pathological P wave dispersion values, compared to baseline characteristics. Conclusion. In patients with CHD, CHF, and persistent AF, the combination of MK and anti-recurrent AF therapy was linked to reduced rates of AF recurrence, as well as to improved CHF FC.